Inhibition of the nucleus accumbens decreases the locomotor response to acute oxycodone exposure in female rats - Midani, Lenah C. (Tufts University. Tisch Library., 2023)
As we try to develop treatments for opioid use disorder, it is important that we understand the complex phenomenon that is opioid use disorder. It is also vital that we explore the involved mechanisms in female rats, which are often excluded in such studies. One of the primary structures implicated in opioid use disorder is the nucleus accumbens, which has been thought to modulate long term expression of the sensitization response. However, this study showed that inhibition of the nucleus accumbens in female rats only reduced sensitization behaviors in those exposed to oxycodone for the first time rather than those who had already become sensitized to oxycodone. This suggests that the nucleus accumbens has more involvement in the development of sensitization than long term expression. This could change the way we approach treatment options for opioid use disorder.; Cummings School of Veterinary Medicine Student Summer Research 2023.